2022
DOI: 10.1108/jwam-10-2022-0069
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive technologies for human resource management: a conceptual framework development and research agenda

Abstract: PurposeDisruptive technologies for human resource management (HRM) lack evidence about synthesizing its antecedents and outcomes in the empirical research landscape. This review study was conducted addressing two objectives: (1) to identify the themes of HRM technology empirically researched and (2) to develop a conceptual framework for the antecedents and outcomes of disruptive technologies for HRM.Design/methodology/approachThis article was positioned as a literature review based on the systematic literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
(197 reference statements)
0
21
0
Order By: Relevance
“…The most common unit of analysis is the keywords that reflect the main content of an article ( Jain et al, 2022b , Jain et al, 2022a ; Callon et al, 1983 ). In the case of finding the common or most minor areas of investigation, this co-occurrence of keywords in articles is taken as the unit of analysis ( Andrlić et al, 2023 ; Aparicio et al, 2019 ; Priyashantha et al, 2021a , Priyashantha et al, 2021c , Priyashantha et al, 2022b ; Priyashantha, 2022 ; Priyashantha, Dahanayake, & Maduwanthi, 2022 ). Thus, the links of such networks can be created using the co-occurrence relationship of such keywords in the articles ( Aparicio et al, 2019) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common unit of analysis is the keywords that reflect the main content of an article ( Jain et al, 2022b , Jain et al, 2022a ; Callon et al, 1983 ). In the case of finding the common or most minor areas of investigation, this co-occurrence of keywords in articles is taken as the unit of analysis ( Andrlić et al, 2023 ; Aparicio et al, 2019 ; Priyashantha et al, 2021a , Priyashantha et al, 2021c , Priyashantha et al, 2022b ; Priyashantha, 2022 ; Priyashantha, Dahanayake, & Maduwanthi, 2022 ). Thus, the links of such networks can be created using the co-occurrence relationship of such keywords in the articles ( Aparicio et al, 2019) .…”
Section: Methodsmentioning
confidence: 99%
“…As a result, by default, the VOSviewer employs association strength normalization and generates a network in a two-dimensional space ( Priyashantha et al, 2022a ; van Eck & Waltman, 2014b ). In that space, significantly linked keywords represented by nodes are found near one another, whereas less significant ones are found far away ( Priyashantha, 2022 ; van Eck & Waltman, 2014a ). The VOSviwer then distributed the nodes to a network of clusters, with highly correlated nodes assigned to the same cluster (X.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Separate systematic literature reviews on gender stereotypes changes (Priyashantha et al, 2021b(Priyashantha et al, , 2021a(Priyashantha et al, , 2021c(Priyashantha et al, , 2021d, work-family conflicts (Priyashantha et al, 2022b), and disruptive HRM technologies (Priyashantha, 2022;Priyashantha et al, 2022a) were conducted based on the empirical publications. They revealed that researchers had not investigated these variables with employee engagement in a holistic model.…”
Section: Introductionmentioning
confidence: 99%
“…The second paper is by Priyashantha (2023) and is entitled “Disruptive Technologies for Human Resource Management: a conceptual framework development and research agenda”. The author’s work helps us understand – and potentially predict – the ways in which digital HRM systems might have major changes on an organisation.…”
mentioning
confidence: 99%